2023
DOI: 10.3389/fcvm.2023.1070616
|View full text |Cite
|
Sign up to set email alerts
|

circRNA, a novel diagnostic biomarker for coronary heart disease

Abstract: ObjectiveThis study aimed to identify the potential diagnostic biomarkers of coronary heart disease (CHD) from exosome-derived circRNA.MethodsThe microarray data of circRNA derived from the exosomes of patients with CHD and mRNA in acute myocardial infarction was retrieved from exoRBase website and GEO database (GSE61144), respectively, to identify the differentially expressed genes (DEGs). Our findings detected the differentially expressed circRNAs and mRNAs and predicted their correlation with microRNAs usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…These findings strongly suggest that exosomal circENC1 is a suitable biomarker for diagnosing plaque stability. Previous studies have identified exosomal circRNAs, including exosomal circ_0043837 28 and circRNA0001785 29 , as biomarkers for cardiovascular diseases such as left atrial appendage (LAA) stroke and coronary heart disease. These diseases are intricately linked to plaque stability.…”
Section: Discussionmentioning
confidence: 99%
“…These findings strongly suggest that exosomal circENC1 is a suitable biomarker for diagnosing plaque stability. Previous studies have identified exosomal circRNAs, including exosomal circ_0043837 28 and circRNA0001785 29 , as biomarkers for cardiovascular diseases such as left atrial appendage (LAA) stroke and coronary heart disease. These diseases are intricately linked to plaque stability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent microarray analysis of exosomes collected from 6 cases of coronary heart disease (CHD) patients and 32 healthy subjects revealed 85 differentially regulated cir-cRNAs, with 4 candidates (circRNA0001785, circRNA0000973, circRNA0001741, and cir-cRNA0003922) being proposed as promising predictive biomarkers for CHD and acute coronary syndrome (ACS) [62]. CircSLC8A1 and circNFIX are another pair of circRNAs relevant to the forensic diagnosis of sudden cardiac death (SCD) and acute ischemic heart disease (IHD).…”
Section: Translatable Circrnas In Heartmentioning
confidence: 99%
“…Thus far, circRNAs have been revealed to play biologically significant roles in regulating tumorigenesis and metastasis in different types of cancer [37][38][39][40][41], brain development and diseases [42][43][44], bone development and diseases [45][46][47][48], myogenesis and myopathies [49,50], aging [51], and many other diseases and biological processes [52][53][54][55][56][57][58]. Another arena in which circRNAs have recently garnered tremendous levels of functional importance is the regulation of cardiovascular development and diseases [59][60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 99%